A predictive tool to evaluate disc brake squeal propensity. Part 3: Parametric design studies. (20th February 2004) - Lee, Y.S.; Brooks, P.C.; Barton, D.C.; Crolla, D.A.
This paper is the last in a series of three that present an integrated numerical approach to the analysis of disc brake squeal. It focuses on the application of the technique to the solution of a number of generic classes of problem encountered by the brake system engineer and the results are related to real world experience. The ability of the methodology to find direct use in such a broad area of application lies in the use of fully parameteriSed solid models to define the initial mechanical system. This flexibility is a powerful feature of the approach that ensures its continued use as a predictive tool. The paper concludes with a critical review of the technique and points to a number of refinement routes